Achieving Target Cemented Femoral Stem Anteversion Using a 3-Dimensional Model - Paul Rebgetz, MBBS, FRACS(Ortho), BPthy; Tom McCarthy, BS ME, MBA; Hamish McLaren, FRACS; Matthew J. Wilson, FRCS(Tr&Orth); Sarah L. Whitehouse, PhD, BSc(Hons); Ross W. Crawford, DPhil (Oxon), FRACS(Orth) (Arthroplasty Today, 2023)
Background: Total hip arthroplasty aims to provide patients with a pain-free and stable hip joint through optimization of biomechanics such as femoral anteversion. There are studies evaluating the limits of cementless stem version, however, none assessing the range of version achieved by a cemented collarless stem. A computed tomography (CT)–based study was performed, utilizing a contemporary robotic planning platform to assess the amount of rotation afforded by a cemented collarless stem, whilst maintaining native biomechanics. Methods: The study utilized 36 cadaveric hips. All had CT scans of the pelvis and hip joints. The CT scans were then loaded into a contemporary robotic planning platform. A stem that restored the patients native femoral offset was selected and positioned in the virtual femur. The stem was rotated while checking for cortical contact at the level of the neck cut. Cortical contact was regarded as the rotation limit, assessed in both anteversion and retroversion. Target range for stem anteversion was 10°-20°. Failure to achieve target version triggered a sequence of adjustments to simulate surgical decisions. Results: Native femoral offset and target version range was obtained in 29 of 36 (80.5%) cases. Following an adjustment sequence, 4 further stems achieved target anteversion with a compromise in offset of 2.3 mm. Overall 33 of 36 (91.7%) stems achieved the target anteversion range of 10°-20°. Conclusions: Target femoral stem anteversion can be achieved using a cemented, collarless stem in a CT-based 3-dimensional model in 80.5% of hips. With a small compromise in offset (mean 2.3 mm), this can be increased to 91.7%.